Dissecting the molecular responses of Sorghum bicolor to Macrophomina phaseolina infection - Bandara, Y.M. Ananda Yapa (Kansas State University, 2017)
Charcoal rot, caused by the necrotrophic fungus, Macrophomina phaseolina (Tassi) Goid., is an important disease in sorghum (Sorghum bicolor (L.) Moench). The molecular interactions between sorghum and M. phaseolina are poorly understood. In this study, a large-scale RNA-Seq experiment and four follow-up functional experiments were conducted to understand the molecular basis of charcoal rot resistance and/or susceptibility in sorghum. In the first experiment, stalk mRNA was extracted from charcoal-rot-resistant (SC599) and susceptible (Tx7000) genotypes and subjected to RNA sequencing. Upon M. phaseolina inoculation, 8560 genes were differentially expressed between the two genotypes, out of which 2053 were components of 200 known metabolic pathways. Many of these pathways were significantly up-regulated in the susceptible genotype and are thought to contribute to enhanced pathogen nutrition and virulence, impeded host basal immunity, and reactive oxygen (ROS) and nitrogen species (RNS)-mediated host cell death. The paradoxical hormonal regulation observed in pathogen-inoculated Tx7000 was characterized by strongly upregulated salicylic acid and down-regulated jasmonic acid pathways. These findings provided useful insights into induced host susceptibility in response to this necrotrophic fungus at the whole-genome scale. The second experiment was conducted to investigate the dynamics of host oxidative stress under pathogen infection. Results showed M. phaseolina’s ability to significantly increase the ROS and RNS content of two charcoal-rot-susceptible genotypes, Tx7000 and BTx3042. Over-accumulation of nitric oxide (NO) in stalk tissues in the pathogen-inoculated susceptible genotypes was confirmed using a NO-specific fluorescent probe and confocal microscopy. Significantly increased malondialdehyde content confirmed the enhanced oxidative stress experienced by the susceptible genotypes after pathogen inoculation. These findings suggested the contribution of oxidative stress-associated induced cell death on charcoal rot susceptibility under infection. In the third functional experiment, the behavior of the sorghum antioxidant system after pathogen inoculation was investigated. M. phaseolina significantly increased the glutathione s-transferase (GST), glutathione peroxidase (GPX), glutathione reductase (GR), and peroxidase activities of the susceptible genotypes (Tx7000, BTx3042) but not in the resistant genotypes (SC599, SC35). Increased activities of these enzymes in susceptible genotypes may contribute to reduced oxidative stress thus lowering charcoal rot susceptibility. The fourth functional experiment was designed to quantify induced host-derived cell wall degrading enzymes (CWDEs) using crude enzyme mixtures from stalks. A gel diffusion assay revealed significantly increased pectinesterase activity in pathogen-inoculated Tx7000 and BTx3042 while significantly increased polygalacturonase activity was determined by absorbance. Fluorimetric determination of cell extracts revealed significantly increased cellulose degrading enzyme activity in M. phaseolina-inoculated Tx7000 and BTx3042. These findings revealed the pathogen’s ability to promote charcoal rot susceptibility in grain sorghum through induced host CWDEs. The last functional study was designed to profile the stalk tissue lipidome of Tx7000 and SC599 after M. phaseolina inoculation using automated direct infusion electrospray ionization-triple quadrupole mass spectrometry (ESI-MS/MS). M. phaseolina significantly decreased the phytosterol, phosphatidylserine, and ox-lipid contents in Tx7000 while significantly increasing stigmasterol:sitosterol ratio. Except for ox-lipid content, none of the above was significantly affected in resistant SC599. Results suggested the lethal impacts of M. phaseolina inoculation on plastid- and cell- membrane integrity and the lipid-based signaling capacity of Tx7000. Findings shed light on the host lipid classes that contribute to induced charcoal rot susceptibility in grain sorghum.
Keywords: Macrophomina phaseolina; Charcoal rot; RNA-Seq; Induced disease susceptibilitySorghum bicolor